A carbon-wrapped cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial and its preparation method and application
By preparing carbon-encapsulated cobalt phosphide electrocatalytic water analytical oxygen nanomaterials, the problems of slow kinetics and high overpotentials of the electrolytic water anode are solved, low overpotential and high catalytic performance under alkaline conditions are achieved, and the development of hydrogen energy is promoted.
Patent Information
- Application Number
- CN202111255173.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-27
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-10-27
AI Technical Summary
During the process of electrolytic hydrogen production, the anode oxygen evolution reaction (OER) is slow and the overpotential is high, resulting in large production energy consumption, limiting the improvement of the overall efficiency of electrolytic water and the development of hydrogen energy.
Carbon-encapsulated cobalt phosphide electrocatalytic water decomposition analytical oxygen nanomaterials are used to change the structure of cobalt-based compounds, reduce the overpotential under alkaline conditions, and improve catalytic performance through the protection of the outer carbon layer and the construction of a conductive network.
It is achieved that the electrolytic hydrolyzed oxygen has a low overpotential under alkaline conditions. It can work stably as an oxygen evolution catalyst, has good catalytic performance, and improves the electrocatalytic efficiency of water decomposition oxygen.
Smart Images

Figure CN115896844B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrocatalytic nanomaterials, and specifically relates to a carbon-wrapped cobalt phosphide electrocatalytic water-to-oxygen decomposition nanomaterial, a preparation method and an application thereof. Background Art
[0002] Today's society is facing many energy and environmental problems. Hydrogen energy is considered to be a clean and pollution-free renewable energy. The current methods of hydrogen production include fossil fuel hydrogen production, biohydrogen production, photocatalytic hydrogen production, and water electrolysis hydrogen production. Among them, water electrolysis hydrogen production has the advantages of low cost, no pollution, high energy efficiency, and high product purity. It is the most promising way to develop renewable energy hydrogen. However, in the water electrolysis process, the anodic oxygen evolution reaction (OER) involves four-electron transfer, which is a kinetically slow process. The overpotential of the oxygen evolution reaction is high and the production energy consumption is high, which limits the improvement of the overall efficiency of water electrolysis and the development of hydrogen energy. Therefore, improving the catalytic activity of the anodic oxygen evolution reaction (OER) in water electrolysis is of great significance to the development of hydrogen energy.
[0003] For the oxygen evolution reaction (OER), the precious metal oxides IrO2 and RuO2 have very efficient electrocatalytic properties, but the reserves of these metal oxides are scarce and their prices are expensive, which seriously restricts the large-scale application of water electrolysis in industrial production. Transition metal cobalt-based compounds are abundant, inexpensive, and have certain oxygen evolution catalytic properties, but there is still a big difference between their oxygen evolution catalytic properties and those of precious metals. It is necessary to change the structure of cobalt-based compounds to improve the electrocatalytic performance of oxygen evolution at the anode of water electrolysis under alkaline conditions. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a carbon-encapsulated cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial, which has low raw material cost, simple process and is convenient for large-scale application.
[0005] The present invention also aims to provide a carbon-wrapped cobalt phosphide electrocatalytic water-water oxygen evolution nanomaterial prepared by the above method. The material has a lower overpotential for water electrolysis and oxygen evolution under alkaline conditions by changing the structure of the cobalt-based compound. As an oxygen evolution catalyst, it can work stably under alkaline conditions and has good catalytic performance.
[0006] The last object of the present invention is to provide the application of the above-mentioned carbon-wrapped cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial in oxygen evolution electrocatalysis in water decomposition.
[0007] The first object of the present invention can be achieved by the following technical solution: A method for preparing a carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial comprises the following steps:
[0008] (1) (NH4)2S2O8 and HCl are mixed and placed in an ice bath, pyrrole (PY) is added dropwise under stirring, and a polymerization reaction is carried out in an ice bath, and the reaction product is washed and dried to obtain black solid powder polypyrrole (PPY);
[0009] (2) taking the polypyrrole (PPY) and CoCl2·6H2O in step (1), adding deionized water to dissolve and mix, reacting under stirring conditions and then drying to obtain a black cobalt-containing polypyrrole (Co-PPY);
[0010] (3) placing the cobalt-containing polypyrrole (Co-PPY) in step (2) in a temperature programmable tube furnace for heat treatment, the heat treatment comprising: heating the temperature to 300°C at a heating rate of 0.8-1.2°C / min at 30°C, maintaining the temperature at 300°C for 180-300 minutes, further heating the temperature to 800°C at a heating rate of 10°C / min, maintaining the temperature at 800°C for 120 minutes, and naturally cooling to room temperature to obtain a precursor cobalt-containing carbon material (Co@NOCs);
[0011] (4) The precursor cobalt-containing carbon material (Co@NOCs) in step (3) and NaH2PO2·H2O are subjected to phosphating heat treatment in a tubular furnace. During the phosphating heat treatment, the tubular furnace is heated to 300-350°C at a heating rate of 2°C / min, maintained at 300-350°C for 1-3 hours, and naturally cooled to room temperature to obtain a carbon-encapsulated cobalt phosphide electrocatalytic water decomposition oxygen material (Co2P@NOCs).
[0012] In the preparation method of the above carbon-wrapped cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial:
[0013] Preferably, in step (1), the dosage ratio of the (NH4)2S2O8 and the HCl is 0.105 g:1 mL, and the concentration of the HCl is 1 mol / L.
[0014] Preferably, the usage ratio of the pyrrole (PY) and the (NH4)2S2O8 is 1 μL:7 mg.
[0015] Preferably, the temperature of the ice bath in step (1) is 0-5°C.
[0016] Preferably, the polymerization reaction time in step (1) is 5 hours.
[0017] Preferably, the cleaning in step (1) is performed using deionized water, anhydrous ethanol and 40 mL of 1 mol / L NH 3 · H 2 O.
[0018] Preferably, the drying in step (1) is forced air drying, the drying temperature is 60 to 80° C., the drying time is 8 to 12 hours, and the drying is complete.
[0019] Preferably, in step (2), the molar ratio of the polypyrrole (PPY) to the CoCl2·6H2O is 2:1.
[0020] In early experiments, the inventors of the present application tried molar ratios of the polypyrrole (PPY) and the CoCl2·6H2O of 8:1, 4:1, 2:1, 1:1, etc., but except for the molar ratio of 2:1, other molar ratios are not easy to be subsequently phosphated to form Co2P@NOCs. Therefore, the present application limits the molar ratio of the polypyrrole (PPY) and the CoCl2·6H2O to 2:1.
[0021] Preferably, the stirring in step (2) is magnetic stirring, and the reaction is carried out under magnetic stirring conditions for 5 to 7 hours before drying.
[0022] More preferably, the stirring in step (2) is magnetic stirring, and the reaction is carried out under magnetic stirring conditions for 6 hours and then dried.
[0023] Preferably, the drying in step (2) is forced air drying, the drying temperature is 60 to 80° C., the drying time is 8 to 12 hours, and the drying is complete.
[0024] The present invention has been found through experiments that after the constant temperature of 800°C for 120 minutes in step (3), the material is naturally cooled to room temperature to obtain a precursor cobalt-containing carbon material (Co@NOCs). If the temperature is lower than 800°C, the cobalt-containing polypyrrole (Co-PPY) is not well carbonized. If the temperature is higher than 800°C, especially above 1000°C, there will be a serious loss of N element, thereby deteriorating the performance of the material. After the constant temperature of 800°C for 120 minutes, a product with better carbonization and more N element retention can be obtained. The more nitrogen elements there are, the more defects there are in the graphite-type carbon, which is more conducive to the catalytic reaction. Therefore, the retention of the N element has a great effect on the performance of the product.
[0025] Therefore, preferably, in step (3), the cobalt-containing polypyrrole (Co-PPY) is placed in a temperature programmable tube furnace for heat treatment under an argon or nitrogen atmosphere, and the heat treatment includes: heating the temperature to 300°C at a heating rate of 1°C / min at 30°C, maintaining the temperature at 300°C for 300 minutes, continuing to heat the temperature to 800°C at a heating rate of 10°C / min, maintaining the temperature at 800°C for 120 minutes, and naturally cooling to room temperature to obtain a precursor cobalt-containing carbon material (Co@NOCs).
[0026] Preferably, the temperature programmable tube furnace in step (3) is a conventional commercially available device, and preferably a temperature programmable tube furnace of model OTF-1200X produced by Hefei Kejing Material Technology Co., Ltd.
[0027] Preferably, in step (4), the mass ratio of the precursor cobalt-containing carbon material (Co@NOCs) to the NaH2PO2·H2O is 1:15-25.
[0028] More preferably, in step (4), the mass ratio of the precursor cobalt-containing carbon material (Co@NOCs) to the NaH2PO2·H2O is 1:20.
[0029] Preferably, in step (4), according to the direction of the airflow, the one that contacts the airflow first is the upstream, and the one that contacts the airflow later is the downstream. The NaH2PO2·H2O is placed upstream of the tubular furnace, and the cobalt-containing carbon material (Co@NOCs) is placed downstream of the tubular furnace.
[0030] More preferably, during the phosphating heat treatment in step (4), the temperature in the tubular furnace is raised to 300°C at a heating rate of 2°C / min, maintained at 300°C for 2 hours, and naturally cooled to room temperature to obtain a carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen material (Co2P@NOCs).
[0031] Step (4) Phosphating heat treatment: By introducing the P element, the precursor cobalt-containing carbon material is changed from Co@NOCs to Co2P@NOCs, and from carbon-encapsulated Co to carbon-encapsulated Co2P, and the overpotential is greatly reduced. Figure 4 From the LSV curve, it can be seen that the overpotential dropped from 399mv to 340mv, which improved the oxygen electrocatalytic performance of water decomposition.
[0032] The above second object of the present invention can be achieved by the following technical solution: A carbon-wrapped cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial is prepared by the above method.
[0033] The third object of the present invention can be achieved by the following technical solution: application of the carbon-wrapped cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial in oxygen evolution electrocatalysis in water decomposition.
[0034] The present invention has the following advantages:
[0035] (1) The preparation method of the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial provided by the present invention has low raw material cost, simple preparation process, and is convenient for large-scale application;
[0036] (2) The carbon-wrapped cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial prepared by the method of the present invention is a tightly bound agglomerated nanoparticle, and the outer carbon layer is tightly cross-linked to construct a conductive network, which helps the material to conduct electricity; in addition, the outer carbon layer can not only prevent the agglomeration and migration of the Co2P nanocore, but also protect the internal nanocore from the influence of the harsh environment, so that it can work stably under alkaline conditions;
[0037] (3) The carbon-wrapped cobalt phosphide electrocatalytic water-to-oxygen decomposition nanomaterial prepared by the method of the present invention has good electrical conductivity. For example, the encapsulation structure formed by the Co2P nanoparticles and the carbon co-doped with N and O in the material can promote the electron transfer in the catalytic process and increase the rate of electron transfer transmission. With Co2P as the catalytic active site, the interaction between the interface between the two can improve the oxygen evolution electrocatalytic activity.
[0038] (4) The carbon-encapsulated cobalt phosphide electrocatalytic water-to-oxygen evolution nanomaterial prepared by the method of the present invention has a low overpotential for water electrolysis and oxygen evolution under alkaline conditions, can work stably as an oxygen evolution catalyst under alkaline conditions, and has good catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 XRD pattern of carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial prepared in Example 1;
[0040] Figure 2 This is a field emission scanning electron microscope (FESEM) image of the carbon-wrapped cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial prepared in Example 1;
[0041] Figure 3 This is a transmission electron microscope (TEM) image of the carbon-encapsulated cobalt phosphide electrocatalytic water-to-oxygen decomposition nanomaterial prepared in Example 1;
[0042] Figure 4 LSV curves of electrochemical oxygen evolution performance test of NOPCs prepared in Comparative Example 1, the precursor Co@NOC prepared in Example 1, 99.9% RuO2 noble metal and carbon-encapsulated cobalt phosphide electrocatalytic water-to-oxygen decomposition nanomaterials (Co2P@NOCs);
[0043] Figure 5 Electrochemical oxygen evolution performance test of NOPCs prepared in Comparative Example 1, precursor Co@NOCs and carbon-encapsulated cobalt phosphide electrocatalytic water-to-oxygen nanomaterials (Co2P@NOCs) prepared in Example 1, and alternating current impedance (EIS) graph;
[0044] Figure 6 Tafel diagram of electrochemical oxygen evolution performance test of NOPCs prepared in Comparative Example 1, precursor Co@NOCs and carbon-encapsulated cobalt phosphide electrocatalytic water-to-oxygen nanomaterials (Co2P@NOCs) prepared in Example 1. DETAILED DESCRIPTION
[0045] The Co2P@NOCs nanomaterial is described in detail below through a specific implementation scheme. The implementation methods of the present invention include but are not limited to this scheme. The raw materials used can be obtained from public commercial channels.
[0046] Example 1
[0047] The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial provided in this embodiment comprises the following steps:
[0048] (1) Preparation of polypyrrole (PPY)
[0049] Add 4.2g (NH4)2S2O8 and 40mL (1mol / L) HCl into a round-bottom flask and mix them together. Place the round-bottom flask in an ice bath at (0-5)°C, add 600μL pyrrole (PY) dropwise while stirring, and polymerize in an ice bath at (0-5)°C for 5 hours. Wash with deionized water, anhydrous ethanol, and 40mL (1mol / L) NH3·H2O, and dry in an 80°C forced air drying oven for 8 hours to obtain a black solid powder polypyrrole (PPY).
[0050] (2) Preparation of cobalt-containing polypyrrole (Co-PPY)
[0051] Take PPY (0.21 g) and CoCl2·6H2O (0.3705 g, M=237.93 g / mol) (the molar ratio of PPY to CoCl2·6H2O is 2:1) into a beaker, add 20 mL of deionized water to dissolve and mix, stir for 6 hours under a magnetic stirrer, and then put it into an 80°C forced air drying oven for 12 hours to obtain black cobalt-containing polypyrrole (Co-PPY).
[0052] (3) Preparation of precursor cobalt-containing carbon materials (Co@NOCs)
[0053] Co-PPY was placed in a temperature programmable tube furnace for heat treatment: the temperature was raised to 300°C at a heating rate of 1°C / min at 30°C, maintained at 300°C for 300 minutes, then raised to 800°C at a rate of 10°C / min, maintained at 800°C for 120 minutes, and then naturally cooled to room temperature to obtain the precursor Co@NOCs.
[0054] (4) Preparation of carbon-coated cobalt phosphide electrocatalytic water-to-oxygen separation materials (Co2P@NOCs)
[0055] Take 0.05g of the precursor Co@NOCs in step (3) and 1g of NaH2PO2·H2O (the mass ratio of Co@NOCs to NaH2PO2·H2O is 1:20) and carry out phosphating heat treatment in a tubular furnace. According to the direction of airflow, the one that contacts the airflow first is the upstream, and the one that contacts the airflow later is the downstream. The NaH2PO2·H2O is placed upstream of the tubular furnace, and the cobalt-containing carbon material (Co@NOCs) is placed downstream of the tubular furnace. The tubular furnace is heated to 300°C at a heating rate of 2°C / min, and then kept at 300°C for 2 hours and then naturally cooled to room temperature to obtain carbon-encapsulated cobalt phosphide electrocatalytic water decomposition oxygen nanomaterial (Co2P@NOCs).
[0056] The carbon-encapsulated cobalt phosphide electrocatalytic water-oxygen separation material (Co2P@NOCs) prepared in Example 1 was subjected to the following test characterizations:
[0057] Figure 1 This is the XRD pattern of the carbon-encapsulated cobalt phosphide electrocatalytic water desorption oxygen material (Co2P@NOCs) prepared in Example 1. The 2θ in the spectrum is 40.72°, 43.20°, 44.22°, and 52.21°, which correspond to the (121), (211), (130), and (002) crystal planes of Co2P (PDF#32-0306), respectively. The diffraction peaks of the XRD spectrum of this material match those of Co2P (PDF#32-0306).
[0058] PDF#32-0306 is one of the standard diffraction peak data of pure phase Co2P. Since Co2P has multiple crystal structures, it will have multiple PDF card standard diffraction peaks. The PDF card is mainly used to compare with the diffraction results of the Co2P@NOCs sample. The qualitative analysis shows that the Co2P@NOCs sample phase is a pure phase and is Co2P, which corresponds to the diffraction peak of the Co2P PDF#32-0306 card.
[0059] Figure 2 This is a field emission scanning electron microscope (FESEM) image of the carbon-encapsulated cobalt phosphide electrocatalytic water-oxygen decomposition material (Co2P@NOCs) prepared in Example 1. Figure 2 It can be seen that the material is a tightly bound cluster of nanoparticles, and the outer carbon layers are tightly connected to form a conductive network, which helps to conduct electricity and thus improve the oxygen electrocatalytic performance of water decomposition.
[0060] Figure 3 This is a transmission electron microscope (TEM) image of the carbon-encapsulated cobalt phosphide electrocatalytic water-oxygen decomposition material (Co2P@NOCs) prepared in Example 1. Figure 3It can be seen that the material is carbon-wrapped Co2P nanoparticles, and the synergistic effect of the carbon layer and the nanoparticles in the core can promote the catalyst's water-decomposition oxygen electrocatalytic reaction.
[0061] Example 2
[0062] The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial provided in this embodiment comprises the following steps:
[0063] (1) Preparation of polypyrrole (PPY)
[0064] Add 4.2g (NH4)2S2O8 and 40mL (1mol / L) HCl into a round-bottom flask and mix them together. Place the round-bottom flask in a (0-5)℃ ice bath, add 600μL pyrrole (PY) dropwise while stirring, and polymerize in an ice bath at (0-5)℃ for 5 hours. Wash with deionized water, anhydrous ethanol, and 40mL (1mol / L) NH3·H2O, and dry in an 80℃ forced air drying oven for 8 hours to obtain black solid powder polypyrrole (PPY).
[0065] (2) Preparation of cobalt-containing polypyrrole (Co-PPY)
[0066] Take PPY (0.21 g) and CoCl2·6H2O (0.3705 g, M=237.93 g / mol) (the molar ratio of PPY to CoCl2·6H2O is 2:1) into a beaker, add 20 mL of deionized water to dissolve and mix, stir for 6 hours under a magnetic stirrer, and then put it into an 80°C forced air drying oven for 12 hours to obtain black cobalt-containing polypyrrole (Co-PPY).
[0067] (3) Preparation of precursor cobalt-containing carbon materials (Co@NOCs)
[0068] Co-PPY was placed in a temperature programmable tube furnace for heat treatment: the temperature was raised to 300°C at a heating rate of 1°C / min at 30°C, maintained at 300°C for 300 minutes, then raised to 800°C at a rate of 10°C / min, maintained at 800°C for 120 minutes, and then naturally cooled to room temperature to obtain the precursor Co@NOCs.
[0069] (4) Preparation of carbon-coated cobalt phosphide electrocatalytic water-to-oxygen separation materials (Co2P@NOCs)
[0070] Take 0.04g of the precursor Co@NOCs in step (3) and 1g of NaH2PO2·H2O (the mass ratio of Co@NOCs to NaH2PO2·H2O is 1:25) and carry out phosphating heat treatment in a tubular furnace. According to the direction of airflow, the one that contacts the airflow first is the upstream, and the one that contacts the airflow later is the downstream. The NaH2PO2·H2O is placed upstream of the tubular furnace, and the cobalt-containing carbon material (Co@NOCs) is placed downstream of the tubular furnace. The tubular furnace is heated to 350°C at a heating rate of 2°C / min, and then kept at 350°C for 2 hours and then naturally cooled to room temperature to obtain carbon-encapsulated cobalt phosphide electrocatalytic water decomposition oxygen nanomaterial (Co2P@NOCs).
[0071] Example 3
[0072] The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial provided in this embodiment comprises the following steps:
[0073] (1) Preparation of polypyrrole (PPY)
[0074] Add 4.2g (NH4)2S2O8 and 40mL (1mol / L) HCl into a round-bottom flask and mix them together. Place the round-bottom flask in a (0-5)℃ ice bath, add 600μL pyrrole (PY) dropwise while stirring, and polymerize in an ice bath at (0-5)℃ for 5 hours. Wash with deionized water, anhydrous ethanol, and 40mL (1mol / L) NH3·H2O, and dry in an 80℃ forced air drying oven for 8 hours to obtain black solid powder polypyrrole (PPY).
[0075] (2) Preparation of cobalt-containing polypyrrole (Co-PPY)
[0076] Take PPY (0.21 g) and CoCl2·6H2O (0.3705 g, M=237.93 g / mol) (the molar ratio of PPY to CoCl2·6H2O is 2:1) into a beaker, add 20 mL of deionized water to dissolve and mix, stir for 6 hours under a magnetic stirrer, and then put it into an 80°C forced air drying oven for 12 hours to obtain black cobalt-containing polypyrrole (Co-PPY).
[0077] (3) Preparation of precursor cobalt-containing carbon materials (Co@NOCs)
[0078] Co-PPY was placed in a temperature programmable tube furnace for heat treatment: the temperature was raised to 300°C at a heating rate of 1°C / min at 30°C, maintained at 300°C for 300 minutes, then raised to 800°C at a rate of 10°C / min, maintained at 800°C for 120 minutes, and then naturally cooled to room temperature to obtain the precursor Co@NOCs.
[0079] (4) Preparation of carbon-coated cobalt phosphide electrocatalytic water-to-oxygen separation materials (Co2P@NOCs)
[0080] Take 0.067g of the precursor Co@NOCs in step (3) and 1g of NaH2PO2·H2O (the mass ratio of Co@NOCs to NaH2PO2·H2O is 1:15) and carry out phosphating heat treatment in a tubular furnace. According to the direction of airflow, the one that contacts the airflow first is the upstream, and the one that contacts the airflow later is the downstream. The NaH2PO2·H2O is placed upstream of the tubular furnace, and the cobalt-containing carbon material (Co@NOC) is placed downstream of the tubular furnace. The tubular furnace is heated to 320°C at a heating rate of 2°C / min, and then kept at 320°C for 2 hours and then naturally cooled to room temperature to obtain carbon-encapsulated cobalt phosphide electrocatalytic water decomposition oxygen nanomaterial (Co2P@NOCs).
[0081] Comparative Example 1
[0082] Preparation of NOPCs nanomaterials
[0083] 0.05g polypyrrole (PPY) and 1g NaH2PO2·H2O (the mass ratio of PPY to NaH2PO2·H2O is 1:20) were taken for phosphating heat treatment in a tube furnace, with NaH2PO2·H2O in the upstream of the tube furnace and PPY in the downstream. The tube furnace was heated to 300°C at a rate of 2°C / min, kept at 300°C for 2 hours, and then naturally cooled to room temperature to obtain NOPCs nanomaterials.
[0084] The following tests were conducted on the precursor Co@NOCs prepared in Example 1, the carbon-encapsulated cobalt phosphide electrocatalytic water-decomposition oxygen material (Co2P@NOCs) and the water-decomposition oxygen electrocatalytic performance of NOPCs prepared in Comparative Example 1:
[0085] The electrochemical performance test adopts the standard three-electrode system of CHI 760E electrochemical workstation. The specific test of the catalytic performance of water decomposition and oxygen production of Co2P@NOCs nanomaterials is as follows:
[0086] The polarization curve (LSV) was tested in 1M KOH solution, with a glassy carbon electrode with a radius of 0.15 cm as the working electrode, Hg / HgO as the reference electrode, and a carbon rod as the counter electrode. The test scan rate was 5 mV / s.
[0087] The electrochemical impedance spectroscopy (EIS) test maintained the original conditions of the electrochemical performance test, with the frequency set from 100,000 Hz to 0.1 Hz and the amplitude set to 0.01 V.
[0088] The Tafel curve is obtained with log(J) and overpotential (η) as the horizontal and vertical coordinates respectively, and the performance of the catalyst Co2P@NOPC in water decomposition and oxygen production under alkaline conditions is evaluated based on the Tafel slope.
[0089] Before the electrochemical performance test, all potentials were corrected with a standard hydrogen electrode. The correction equation is: E RHE =E HgO +0.0592pH+E θ Hg / HgO (E θ Hg / HgO =0.098V).
[0090] The electrochemical oxygen evolution performance test of NOPCs prepared in comparative example 1, the precursor Co@NOCs prepared in example 1, 99.9% RuO2 noble metal and carbon-wrapped cobalt phosphide electrocatalytic water-to-oxygen nanomaterials (Co2P@NOCs) is shown in the LSV diagram. Figure 4 As shown, the scan rate of the test is 5mV / s.
[0091] from Figure 4 It can be seen that the oxygen evolution current density of the Co2P@NOCs water splitting anode is 10 mA / cm 2 When , the overpotential is 330mV.
[0092] The electrochemical oxygen evolution performance test of NOPCs prepared in comparative example 1, the precursor Co@NOC prepared in example 1, and the carbon-encapsulated cobalt phosphide electrocatalytic water-to-oxygen nanomaterial (Co2P@NOCs) is shown in the EIS diagram. Figure 5 shown.
[0093] Depend on Figure 5 It can be seen that Co2P@NOCs has a smaller electron transfer resistance compared with NOPCs and Co@NOCs.
[0094] The electrochemical oxygen evolution performance of the NOPC prepared in Comparative Example 1, the precursor Co@NOCs prepared in Example 1, and the carbon-encapsulated cobalt phosphide electrocatalytic water-to-oxygen nanomaterial (Co2P@NOCs) was tested. The Tafel plot of overpotential (η) versus log (j) is shown in FIG. Figure 6 As shown, the kinetic performance of the oxygen evolution reaction of the catalyst was evaluated by obtaining the Tafel slope.
[0095] Depend on Figure 6 It can be seen that compared with NOPC and Co@NOCs, Co2P@NOCs has a smaller Tafel slope of 97 mV / dec.
[0096] The definition of overpotential is: the difference between the electrode potential when the electrode reaction deviates from equilibrium and the electrode potential at equilibrium. It means the extra energy required to maintain the reaction rate during the electrode reaction. The larger the overpotential, the more energy is required during the reaction and the poorer the catalytic performance. On the contrary, the lower the overpotential, the closer it is to the equilibrium potential, the better the catalytic performance and the less extra energy required.
[0097] Impedance reaction is the speed of electrocatalyst electrode kinetics and interface reaction. The smaller the impedance, the faster the electrocatalyst electrode kinetics and interface reaction, and the faster the electron transfer rate.
[0098] The Tafel slope reflects the speed of the intrinsic reaction kinetics. The smaller the Tafel slope, the faster the reaction kinetics.
[0099] The material has a small impedance and a small Tafel slope, which can further illustrate that the material has good catalytic performance. The material has a low overpotential, and low overpotential is the key. Other factors such as small impedance and small Tafel slope can assist in proving the low overpotential.
[0100] Therefore, the Co2P@NOCs in the present application has a lower overpotential, which means that less energy is required in the catalytic process; the impedance is small, so the electrocatalyst electrode kinetics and interfacial reaction are faster, and the electron transfer rate is faster during the water-to-oxygen decomposition process; the Tafel slope is small, so the reaction kinetics are fast. In summary, the Co2P@NOCs in the present application has good water-to-oxygen decomposition catalytic performance.
[0101] The present invention further Figure 4 The LSV curve of 99.9% RuO2 precious metal is added to the Figure 4 It can be seen that at a current density of 10 mA cm -2 The overpotential of the Co2P@NOCs in the present application is 330 mV, and the overpotential of 99.9% RuO2 is 240 mV. It can be seen that the catalytic performance of the Co2P@NOCs in the present application is close to that of the precious metal RuO2. However, the Co2P@NOCs in the present application has abundant raw material reserves, low prices, simple and easy-to-control preparation process, and is convenient for industrial production and large-scale application.
[0102] Therefore, the cobalt-based phosphide oxygen evolution electrocatalytic nanomaterial in the present invention is composed of tightly bound agglomerated nanoparticles. The heteroelement-doped carbon in the material has good conductivity, which can promote electron transfer in the catalytic process and is conducive to exposing more active sites. The Co2P nanoparticles are wrapped in the carbon material, and Co2P is the catalytic active site. The core-shell interaction between the interface between the nanoparticle core Co2P and the carbon material shell can increase the electron transfer rate, thereby improving the water-decomposition oxygen electrocatalytic activity.
[0103] It should be pointed out that the above embodiments are only further explanations of the present invention rather than limitations, and any adjustments or changes by those skilled in the art within the meaning and scope equivalent to the technical solution of the present invention should be deemed to be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-coated cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial, characterized in that The following steps are involved: (1) Mix (NH4)2S2O8 and HCl and place in an ice bath, add pyrrole PY dropwise under stirring, and carry out polymerization reaction in an ice bath. Wash and dry the reaction product to obtain black solid powder polypyrrole PPY; (2) taking the polypyrrole PPY and CoCl2·6H2O in step (1), adding deionized water to dissolve and mix, reacting under stirring conditions and then drying to obtain black cobalt-containing polypyrrole Co-PPY; (3) placing the cobalt-containing polypyrrole Co-PPY in step (2) in a temperature programmable tube furnace for heat treatment, the heat treatment comprising: heating the temperature to 300°C at a heating rate of 0.8-1.2°C / min at 30°C, maintaining the temperature at 300°C for 180-300 minutes, further heating the temperature to 800°C at a heating rate of 10°C / min, maintaining the temperature at 800°C for 120 minutes, and naturally cooling to room temperature to obtain a precursor cobalt-containing carbon material Co@NOCs; (4) The precursor cobalt-containing carbon material Co@NOCs and NaH2PO2·H2O in step (3) are subjected to phosphating heat treatment in a tubular furnace. During the phosphating heat treatment, the tubular furnace is heated to 300-350°C at a heating rate of 2°C / min, kept at 300-350°C for 1-3 hours, and naturally cooled to room temperature to obtain carbon-encapsulated cobalt phosphide electrocatalytic water decomposition oxygen nanomaterial Co2P@NOCs.
2. The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial according to claim 1, characterized in that: In step (1), the dosage ratio of (NH4)2S2O8 to HCl is 0.105 g:1 mL, the concentration of HCl is 1 mol / L, and the dosage ratio of pyrrole PY to (NH4)2S2O8 is 1 μL:7 mg.
3. The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial according to claim 1, characterized in that: The temperature of the ice bath in step (1) is 0-5°C; the polymerization reaction time in step (1) is 5 hours; the washing in step (1) is performed by using deionized water, anhydrous ethanol and 40 mL of 1 mol / L NH3·H2O for washing, and the drying is performed by forced air drying at a temperature of 60-80°C for a drying time of 8-12 hours.
4. The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial according to claim 1, characterized in that: In step (2), the molar ratio of the polypyrrole PPY to the CoCl2·6H2O is 2:
1.
5. The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial according to claim 1, characterized in that: The stirring in step (2) is magnetic stirring, and the reaction is carried out under magnetic stirring conditions for 5 to 7 hours before drying; the drying in step (2) is forced air drying, the drying temperature is 60 to 80° C., the drying time is 8 to 12 hours, and the drying is complete.
6. The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial according to claim 1, characterized in that: In step (3), the cobalt-containing polypyrrole Co-PPY is placed in a temperature programmable tube furnace for heat treatment under an argon or nitrogen atmosphere. The heat treatment includes: heating the temperature to 300°C at a heating rate of 1°C / min at 30°C, maintaining the temperature at 300°C for 300 minutes, further heating the temperature to 800°C at a heating rate of 10°C / min, maintaining the temperature at 800°C for 120 minutes, and naturally cooling to room temperature to obtain a precursor cobalt-containing carbon material Co@NOCs.
7. The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial according to claim 1, characterized in that: In step (4), the mass ratio of the precursor cobalt-containing carbon material Co@NOCs to the NaH2PO2·H2O is 1:15-25.
8. The method for preparing the carbon-encapsulated cobalt phosphide electrocatalytic water-desorption oxygen nanomaterial according to claim 1, characterized in that: In step (4), according to the direction of the airflow, the one that contacts the airflow first is the upstream, and the one that contacts the airflow later is the downstream. The NaH2PO2·H2O is placed upstream of the tubular furnace, and the cobalt-containing carbon material Co@NOCs is placed downstream of the tubular furnace. During the phosphating heat treatment in step (4), the tubular furnace is heated to 300°C at a heating rate of 2°C / min, kept at 300°C for 2 hours, and naturally cooled to room temperature, thereby obtaining the carbon-encapsulated cobalt phosphide electrocatalytic water decomposition oxygen nanomaterial Co2P@NOCs.
9. A carbon-encapsulated cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial, characterized by: The method is prepared by any one of claims 1 to 8.
10. Application of the carbon-encapsulated cobalt phosphide electrocatalytic water-decomposition oxygen nanomaterial according to claim 9 in electrocatalysis of oxygen evolution in water decomposition.
Citation Information
Patent Citations
Carbon-carried multi-metal polypyrrole oxygen reduction catalyst and preparation method thereof
CN102790223A
Method for synthesizing carbon-supported cobalt polypyrrole oxygen reduction catalyst by alternating current one-step method
CN103341367A